Abdominal Ultrasound Assists the Diagnosis and Management of Necrotizing Enterocolitis. (October 2021) - Chan, Belinda; Gordon, Sasha; Yang, Michelle; Weekes, Jennifer; Dance, Logan
Abstract : Background: Abdominal x-ray (KUB) routinely aids in detecting necrotizing enterocolitis (NEC), one of the most serious neonatal intestinal diseases. However, a KUB may miss up to 50% of the early signs of NEC. Recent advances in abdominal ultrasound (AUS) can expedite this diagnosis and improve clinical management. Purposes: To illustrate AUS findings that suggest NEC through 3 case examples. To review current literature regarding advantages and limitations of AUS compared with KUB. Results: The added visualization of intra-abdominal structures with AUS compared with KUB improves the diagnosis and management of NEC. Some AUS features are highly suggestive of impending bowel perforation, while others can confirm bowel perforation despite a negative radiograph. Implications for Practice: AUS expedites time to diagnosis of NEC and helps to stratify patients who may fail medical management and require surgical intervention. Implications for research: More quality improvement studies are needed to validate an AUS protocol for the management of NEC. Advances in technology, such as contrast-enhanced ultrasound, may improve NEC detection with AUS in the future. Video Abstract available at https://journals.lww.com/advancesinneonatalcare/Pages/videogallery.aspx . Abstract : Supplemental Digital Content is Available in the Text.